1997
DOI: 10.1002/(sici)1099-1263(199711/12)17:6<369::aid-jat449>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Studies on rat thyroid after oral administration of mancozeb: morphological and biochemical evaluations

Abstract: Mancozeb, an ethylenebisdithiocarbamate (EBDC), has been studied for its effects on rat thyroid. Single oral administration of mancozeb at different concentrations (9600, 12 000, 15 000 and 18 750 mg kg−1 body wt) has derived the oral LD50 value as 15 000 mg kg−1 body wt. in male rats. Mancozeb at repeated oral doses of 500, 1000 and 1500 mg kg−1 day−1 for periods of 30, 90, 180 and 360 days has produced dose‐dependent signs of toxicity and death of animals. The fungicide caused a significant increase in thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…The abusive use of such compounds in agriculture has mobilized public concern because of the harmful potential of such substances in the environment and in the food chain representing a risk for human health (EFSA, 2009). A major toxicological concern with respect to mancozeb and other dithiocarbamates is its primary metabolite, ethylene thiourea (ETU), shown to cause structural and functional alterations of gonads and thyroids of humans (Kackar et al, 1997;Baligar et al, 2001). Ethylene thiourea is very soluble and moderately mobile in the environment, it potentially could be found in drinking water from both surface water and groundwater sources close to some farm lands.…”
mentioning
confidence: 99%
“…The abusive use of such compounds in agriculture has mobilized public concern because of the harmful potential of such substances in the environment and in the food chain representing a risk for human health (EFSA, 2009). A major toxicological concern with respect to mancozeb and other dithiocarbamates is its primary metabolite, ethylene thiourea (ETU), shown to cause structural and functional alterations of gonads and thyroids of humans (Kackar et al, 1997;Baligar et al, 2001). Ethylene thiourea is very soluble and moderately mobile in the environment, it potentially could be found in drinking water from both surface water and groundwater sources close to some farm lands.…”
mentioning
confidence: 99%
“…It was also reported that higher dose of Mancozeb have negative effect on plant growth and activity of mycorrhizal symbiosis (Saleh 2006, Chaurasia 2014. According to Kackar et al (1997) and Mirkovic et al (2015) chronic oral feeding of Mancozeb has produced dose dependent toxicity and death of animal by structural and functional changes like significant increase in thyroid, body weight ratio and histopathological changes. Easton et al (2001) reported that by the effect of Mancozeb fungicide novel proteins being induced and stress were increased.…”
Section: Resultsmentioning
confidence: 99%
“…Mancozeb is reported to cause teratogenic, carcinogenic and goitrogenic effects on mammals. Ethylene thio urea (ETU), carbon disulphide (CS 2 ), thio urea etc are metabolites produced in degradation of Mancozeb reported to be responsible for inducing thyroid toxicity and neurotoxicity (Kackar et al 1997, Domico et al 2007, Miller et al 2009. ETU is reported to cause ground water pollution due to its high solubility in water (Belpoggi et al 2002, Srivastava & Singh 2013.…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that organophosphate pesticides affects implantation, gestation, foetal growth, and abnormalities in mammals and development in birds 21,22) . It has also been reported that mancozeb has shown to produce significant toxicological effects on thyroid glands, chromosomes and has adverse effects on fertility but not embryotoxicity 4,6,7) . Mehrotra et al 23) have suggested that the mancozeb shows mutagenic or carcinogenic activity in mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its low acute toxicity mancozeb has been shown to produce adverse effects in fertilization, damage to liver, kidney, central nervous system and chromosomes of bone marrow cells in mice [4][5][6][7] . Exposure to mancozeb affects the blood glucose, globulin levels and pathological changes in different organs of rats 8) .…”
mentioning
confidence: 99%